Deciphering alternative splicing patterns during cell fate transition of fast chemical reprogramming - Yunkun Lu; Kainan Lin; Yeling Ruan; Junjie Li; Huizhen Zhang; Tianyuan Pan; Qianqian Wang; Lianyu Lin; Sijie Feng (BMC Biology)
Abstract Background Alternative splicing (AS) is a substantial contributor to the high complexity of transcriptomes in multicellular eukaryotes. Fast chemical reprogramming (FCR) system is an innovative approach that facilitates the rapid transition of somatic cells into induced pluripotent stem cells (iPSCs). Results In this study, we used the FCR system to delve into the dynamics of AS during cell fate transition. The trajectory of FCR, as characterized by gene expression profiles, consistently aligned with that observed in AS patterns, revealing a complex interplay between AS and gene expression regulation. Additionally, we discovered that the exon exclusion events were more prevalent than the exon inclusion events, indicating a predominant mode of splicing regulation during FCR. Compared to transcription factor-induced reprogramming (TFR), FCR showed a distinct AS pattern, underscoring the unique regulatory mechanisms governing AS in each reprogramming system. Further investigation uncovered polypyrimidine tract-binding protein 3 (Ptbp3) as an important splicing factor, possibly participating in epigenetic regulation in late stage of FCR by affecting AS of epigenetic regulators. Moreover, we found an abundance of intron retention events caused by decrease in spliceosome activity, potentially contributing to the downregulation of key diapause-related genes in the middle and late stages of FCR. Conclusions This research provided a comprehensive characterization of AS during FCR, highlighting the pivotal roles of AS in regulating cell fate transitions. Our findings advanced the understanding of the molecular mechanisms governing cell fate decisions and offered new insights into the potential of FCR for regenerative medicine and therapeutic applications.